Cardiovascular Safety of Hydroxychloroquine in US Veterans With Rheumatoid Arthritis. Issue 9 (6th August 2021) - Faselis, Charles; Zeng‐Treitler, Qing; Cheng, Yan; Kerr, Gail S.; Nashel, David J.; Liappis, Angelike P.; Weintrob, Amy C.; Karasik, Pamela E.; Arundel, Cherinne; Boehm, Denise; Heimall, Michael S.; Connell, Lawrence B.; et al.
Abstract : Objective: Hydroxychloroquine (HCQ) may prolong the QT interval, a risk factor for torsade de pointes, a potentially fatal ventricular arrhythmia. This study was undertaken to examine the cardiovascular safety of HCQ in patients with rheumatoid arthritis (RA). Methods: We conducted an active comparator safety study of HCQ in a propensity score–matched cohort of 8, 852 US veterans newly diagnosed as having RA between October 1, 2001 and December 31, 2017. Patients were started on HCQ (n = 4, 426) or another nonbiologic disease‐modifying antirheumatic drug (DMARD; n = 4, 426) after RA diagnosis, up to December 31, 2018, and followed up for 12 months after therapy initiation, up to December 31, 2019. Results: Patients had a mean ± SD age of 64 ± 12 years, 14% were women, and 28% were African American. The treatment groups were balanced with regard to 87 baseline characteristics. There were 3 long QT syndrome events (0.03%), 2 of which occurred in patients receiving HCQ. Of the 56 arrhythmia‐related hospitalizations (0.63%), 30 occurred in patients in the HCQ group (hazard ratio [HR] associated with HCQ 1.16 [95% confidence interval (95% CI) 0.68–1.95]). All‐cause mortality occurred in 144 (3.25%) and 136 (3.07%) of the patients in the HCQ and non‐HCQ groups, respectively (HR associated with HCQ 1.06 [95% CI, 0.84–1.34]). During the first 30 days of follow‐up, there were no long QT syndrome events, 2 arrhythmia‐related hospitalizations (none in the HCQ group), and 13 deaths (6 in the HCQ group). Conclusion: Our findings indicate that the incidence of long QT syndrome and arrhythmia‐related hospitalization is low in patients with RA during the first year after the initiation of HCQ or another nonbiologic DMARD. We found no evidence that HCQ therapy is associated with a higher risk of adverse cardiovascular events or death.